POSITIVE: Perfusion imaging selection of ischemic stroke patients for endovascular therapy. (25th February 2021) - Mocco, J; Siddiqui, Adnan H; Fiorella, David; Alexander, Michael J; Arthur, Adam S; Baxter, Blaise W; Budzik, Ronald F; Froehler, Michael T; Hanel, Ricardo A; Lena, Jonathan; Persaud, Steven; Puri, Ajit S; et al.
Abstract : Background: The PerfusiOn imaging Selection of Ischemic sTroke patIents for endoVascular thErapy (POSITIVE) trial was designed to evaluate functional outcome in patients with emergent large vessel occlusion (ELVO) presenting within 0–12 hours with pre-specified bifurcated arms of early and late window presentation, who were selected for endovascular thrombectomy with non-vendor specific commercially available perfusion imaging software. Recent trials demonstrating the benefit of thrombectomy up to 16–24 hours following ELVO removed equipoise to randomize late window ELVO patients and therefore the trial was halted. Methods: Up to 200 patients were to be enrolled in this FDA-cleared, prospective, randomized, multicenter international trial to compare thrombectomy and best medical management in patients with ELVO ineligible for or refractory to treatment with IV tissue plasminogen activator (IV-tPA) selected with perfusion imaging and presenting within 0–12 hours of last seen normal. The primary outcome was 90-day clinical outcome as measured by the raw modified Rankin Scale (mRS) with scores 5 and 6 collapsed (mRS shift analysis). Results: The POSITIVE trial suspended enrollment with the release of results from the DAWN trial and was stopped after the release of the DEFUSE 3 trial results. Thirty-three patients were enrolled (21 for medical management and 12 for thrombectomy). Twelve of the 33 patients were enrolled in the 6–12 hour cohort. Despite the early cessation, the primary outcome demonstrated statistically significant superior clinical outcomes for patients treated with thrombectomy (P=0.0060). The overall proportion of patients achieving an mRS score of 0–2 was 75% in the thrombectomy cohort and 43% in the medical management cohort (OR 4.00, 95% CI 0.84 to 19.2). Conclusion: POSITIVE supports the already established practice of delayed thrombectomy for appropriately selected patients presenting within 0–12 hours selected by perfusion imaging from any vendor. The results of the POSITIVE trial are consistent with other thrombectomy trials. The statistically significant effect on functional improvement, despite the small number of patients, reinforces the robust benefits of thrombectomy. Clinical trial registration: NCT01852201